FIRST EVALUATION OF GENOTOXICITY OF MACAÉ (RJ) ESTUARINE WATERS - da Conceição, Moisés Basilio; da Costa, Vitor Oliveira; Molisani, Maurício Mussi; Weber, Laura Isabel (Arquivos de Ciências do Mar, 2018)
Low levels of contamination were detected recently on Macaé estuarine waters showing effects in aquatic organisms at different levels. Nonetheless, genotoxicity was not yet evaluated for these waters. A preliminary study was performed using zebrafish Danio rerio by exposing this species to Macaé River estuarine waters. DNA and chromosome damage was evaluated by the comet assay, after 24h and 48h of exposure; and by the micronucleus test, after 72 h and seven days of exposure. The results showed DNA damage (% Tail DNA) 5.1-fold higher in fish exposed to estuarine waters than in controls after 48 h of exposure; and significantly higher number of micronuclei/thousand (10-12) in fish exposed to estuarine waters than in controls after three and seven days of exposure. The results of the present study, although preliminary, evidenced genotoxicity of the estuarine waters from the Macaé River, indicating that genotoxicity was at levels to induce DNA and chromosome damage in adult fish.